Ethical Behavior in Scientific Publications: Misconduct and Preventive Actions - Zúñiga Vargas, Juan Pablo (2019)
This article encompasses a bibliographic review of the main types of scientific misconduct in publications based on a search of academic databases and search engines.  The search was performed publications regarding scientific editorial misconduct in research articles. The data obtained was analyzed and each example of misbehavior was classified according to author, editor and peer reviewers. For preventive purposes, formative assessments of undergraduate and graduate students understanding of research methodology are recommended. In addition, journal editorial boards must adopt measures, such as establish a code of ethics and statement of originality, to ensure ethical behavior when publishing research articles.